A multi-attribute model of Japanese consumer's purchase intention for GM foods - Renee B. KIM (Agricultural Economics (AGRICECON), 2010)
This study illustrates that consumers' GM food purchase decision is determined by a set of correlated variables. The interrelationship among the GM food purchase decision determinants is examined conceptually and empirically with a multi-attribute model, describing this interrelationship. Consumers' attitudes toward subjects such as innovation, science & technology as well as their trust towards the government's regulatory system of food safety and GM food are strong indicators of the consumers' GM food purchase decision. Given the limited availability of GM foods in the market which leads to a lack of understanding and experience of GM foods, consumers' knowledge and their search for information on food label appear to be weaker determinants of the GM food purchase decision for consumers.